Neuromelanin‐Sensitive Magnetic Resonance Imaging Using DANTE Pulse. Issue 4 (14th December 2020) - Oshima, Sonoko; Fushimi, Yasutaka; Okada, Tomohisa; Nakajima, Satoshi; Yokota, Yusuke; Shima, Atsushi; Grinstead, John; Ahn, Sinyeob; Sawamoto, Nobukatsu; Takahashi, Ryosuke; Nakamoto, Yuji
Abstract: Background: Neuromelanin‐sensitive magnetic resonance imaging techniques have been developed but currently require relatively long scan times. The aim of this study was to assess the ability of black‐blood delay alternating with nutation for tailored excitation‐prepared T1‐weighted variable flip angle turbo spin echo (DANTE T1‐SPACE), which provides relatively high resolution with a short scan time, to visualize neuromelanin in the substantia nigra pars compacta (SNpc). Methods: Participants comprised 49 healthy controls and 25 patients with Parkinson's disease (PD). Contrast ratios of SNpc and hyperintense SNpc areas, which show pixels brighter than thresholds, were assessed between DANTE T1‐SPACE and T1‐SPACE in healthy controls. To evaluate the diagnostic ability of DANTE T1‐SPACE, the contrast ratios and hyperintense areas were compared between healthy and PD groups, and receiver operating characteristic analyses were performed. We also compared areas under the curve (AUCs) between DANTE T1‐SPACE and the previously reported gradient echo neuromelanin (GRE‐NM) imaging. Each analysis was performed using original images in native space and images transformed into Montreal Neurological Institute space. Values of P  < 0.05 were considered significant. Results: DANTE T1‐SPACE showed significantly higher contrast ratios and larger hyperintense areas than T1‐SPACE. On DANTE T1‐SPACE, healthy controls showed significantly higher contrast ratios and larger hyperintense areas than patients with PD. Hyperintense areas in native space analysis achieved the best AUC (0.94). DANTE T1‐SPACE showed AUCs as high as those of GRE‐NM. Conclusions: DANTE T1‐SPACE successfully visualized neuromelanin of the SNpc and showed potential for evaluating PD. © 2020 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society Abstract : April Infographic: Neuromelanin‐Sensitive Magnetic Resonance Imaging Using DANTE Pulse